2013
DOI: 10.1186/1471-2229-13-200
|View full text |Cite
|
Sign up to set email alerts
|

Arabidopsis CROWDED NUCLEI (CRWN) proteins are required for nuclear size control and heterochromatin organization

Abstract: BackgroundPlant nuclei superficially resemble animal and fungal nuclei, but the machinery and processes that underlie nuclear organization in these eukaryotic lineages appear to be evolutionarily distinct. Among the candidates for nuclear architectural elements in plants are coiled-coil proteins in the NMCP (Nuclear Matrix Constituent Protein) family. Using genetic and cytological approaches, we dissect the function of the four NMCP family proteins in Arabidopsis encoded by the CRWN genes, which were originall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
216
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 142 publications
(238 citation statements)
references
References 38 publications
(52 reference statements)
14
216
1
Order By: Relevance
“…This widely observed correlation between stomatal size, guard cell nucleus size, and plant genome size has prompted the hypothesis (yet to be tested comprehensively) that selection for higher or lower stomatal conductance involves coselection for correlated changes in S, D, and genome size (Franks et al, 2012a(Franks et al, , 2012b. The role of factors that determine nucleus size and architecture also must be considered, including coiled-coil proteins in the Nuclear Matrix Constituent Protein family (Wang et al, 2013). If genome size does impose a constraint on stomatal size and gas-exchange capacity, then the wide range of angiosperm genome size could be a significant contributing factor in the current dominance of angiosperms across diverse landscapes and climates.…”
Section: Stomatal Size Density and Conductance Through Deep Timementioning
confidence: 99%
“…This widely observed correlation between stomatal size, guard cell nucleus size, and plant genome size has prompted the hypothesis (yet to be tested comprehensively) that selection for higher or lower stomatal conductance involves coselection for correlated changes in S, D, and genome size (Franks et al, 2012a(Franks et al, , 2012b. The role of factors that determine nucleus size and architecture also must be considered, including coiled-coil proteins in the Nuclear Matrix Constituent Protein family (Wang et al, 2013). If genome size does impose a constraint on stomatal size and gas-exchange capacity, then the wide range of angiosperm genome size could be a significant contributing factor in the current dominance of angiosperms across diverse landscapes and climates.…”
Section: Stomatal Size Density and Conductance Through Deep Timementioning
confidence: 99%
“…Thus, deficiency of a lamina component can cause genetic diseases and inhibit growth (Dauer and Worman, 2009). Wang et al (2013) reported their inability to isolate a null mutant lacking all four CRWN genes (Wang et al, 2013). By contrast, KAKU4 is not essential, which suggests that plants might have acquired nonessential components of the lamina-like structure.…”
Section: (H) To (L) Electron Micrographs Of Nuclei In Root Cells Of Smentioning
confidence: 99%
“…Arabidopsis has four NMCP homologs called CROWDED NUCLEI (CRWN) (Wang et al, 2013), formerly named LITTLE NUCLEI (Dittmer et al, 2007;Ciska and Moreno Diaz de la Espina, 2013;Sakamoto and Takagi, 2013). Arabidopsis mutants crwn1 and crwn4 displayed aberrantly small and spherical nuclei in mature epidermal cells (Dittmer et al, 2007;Sakamoto and Takagi, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the associations observed between both parameters may reflect their adaptations to particular ecological conditions. On the other hand, the results showing reduction in nucleus size to be negatively correlated with heterochromatin content appears intriguing, although this effect has recently been demonstrated (Wang et al, 2013) in another organism, specifically in the Arabidopsis mutant Crowded Nucleus (CRWN). In the case of increasing nuclear size, the evidence available in animals and plants has revealed a positive correlation, although mainly with nuclear DNA content (Swanson et al, 1981;Jovtchev et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…According to the evidence available in Arabidopsis, nuclear changes induced by heterochromatin cannot be ruled out, given the identification of various genes that specifically control such processes (Fransz et al, 2003;Wang et al, 2013). For example, in the ddm1 mutant, it is observed that the heterochromatin content is significantly reduced in the nucleus (-30%) in comparison to the wild type.…”
Section: Discussionmentioning
confidence: 99%